Pengembangan Media Pembelajaran Berbasis Video Animasi Stop Motion Pada Tema 6 Subtema 2 “Perpindahan Kalor Di Sekitar Kita” Kelas V SDN 173468 Pulogodang T.A 2022/2023 - Sri Devi Simanullang; Wildansyah Lubis (FKIP, Universitas Palangka Raya, 2024)
This research was conducted based on the problems experienced in the learning process, namely conventional learning methods and rarely using learning media which causes students to feel bored and less interested in following the learning process without using learning media in the learning process in class. Students are more interested in learning media that displays moving images and sound (audiovisual/video). The purpose of this study was to: (1) to see the validity level of Stop Motion Animation Video Learning Media on Theme 6 Sub-theme 2